2019
DOI: 10.1002/jbm.b.34479
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional electrospun nanofibrous scaffolds for bone tissue engineering

Abstract: Electrospinning technology has been widely used in the past few decades to prepare nanofibrous scaffolds that mimic extracellular matrices. However, traditional two‐dimensional (2D) electrospun nanofibrous mats still have some inherent disadvantages for bone tissue engineering, such as limited cell infiltration and lack of three‐dimensional (3D) structure. The development of 3D electrospun scaffolds with larger pore sizes and porosity provides new perspectives for electrospinning‐based tissue engineering scaff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 100 publications
0
52
0
Order By: Relevance
“…Therefore, it would be useful to determine the optimal mixing ratio of DWJM/PCL. Furthermore, the construction of a 3D tubular scaffold with controllable lumen diameter and wall thickness from 2D nanofibrous membranes is a technological problem that should be addressed before its further application in trachea tissue engineering 15. At present, limited progress has been achieved in addressing this problem 16.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it would be useful to determine the optimal mixing ratio of DWJM/PCL. Furthermore, the construction of a 3D tubular scaffold with controllable lumen diameter and wall thickness from 2D nanofibrous membranes is a technological problem that should be addressed before its further application in trachea tissue engineering 15. At present, limited progress has been achieved in addressing this problem 16.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the construction of a 3D tubular scaffold with controllable lumen diameter and wall thickness from 2D nanofibrous membranes is a technological problem that should be addressed before its further application in trachea tissue engineering. [15] At present, limited progress has been achieved in addressing this problem. [16] More importantly, no study to date has achieved segmental tracheal defect repair using a 2D DWJM/PCL nanofibrous membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging the beneficial features, the electrospun nanofibers offers great possibility in the regeneration of various tissues in the human body as depicted in the Figure 7 [101]. Therefore, to date enormous progress have shown that the electrospun based scaffolds are greatly enhanced the repair/regeneration of different of tissues (e.g., bone, skin, nerve, heart, vascular and muscoskeletal system) due to its inherent properties of large surface area, porosity, stacking/pattering nature, alignment, mechanical strength, complex interface topology and easy functionalization nature [31,47,[102][103][104][105][106][107][108]. Therefore, we evidently discuss potential of electrospun nanofibers in the engineering of various tissues in the following sections.…”
Section: Electrospun Nanofibers In Tissue Engineering Applicationmentioning
confidence: 99%
“…Nanofibers are 1D nanostructured materials with some distinctive characteristics, such as large surface areas, well-controlled composition, flexibility, tunable porosity, ease of surface functionalization, and high mechanical/thermal properties which make them suitable for a number of different applications such as energy harvesting and storage [1,2], filtration [3,4], sensors [5,6], tissue engineering [7][8][9], wound healing [10,11], drug delivery [12,13], polymer reinforcement [14,15], and so on.…”
Section: Introductionmentioning
confidence: 99%